Literature Review: Effect of AIUEO Therapy on Speaking Ability in Non-Hemorrhagic Stroke Patients - Nurani, Rahmawati Dian; Khomsah, Ida Yatun (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: AIUEO therapy is a speech therapy that can help improve speech so that others can understand it. The method of this therapy is to move the lips, facial muscles and tongue by pronouncing the letters given such as A, I, U, E, O. The purpose of the literature review was to find references related to the effect of AIUEO therapy on the ability to speak in non-hemorrhagic stroke patients. Method: This literature review uses the PICOT framework method. Result: The results of the analysis that have been carried out in the article are known to have an effect after AIOUEO therapy on respondents who experience verbal communication disorders. AIUEO therapy is a form of rehabilitation therapy to improve the ability to speak in non-hemorrhagic stroke patients. Conclusion: AIUEO therapy has the effectiveness of being used in improving speech in non-hemorrhagic stroke patients.